TRANSETHOSOMES AS BREAKTHROUGH TOOL FOR CONTROLLED TRANSDERMAL DELIVERY OF DEXKETOPROFEN TROMETAMOL: DESIGN, FABRICATION, STATISTICAL OPTIMIZATION, IN VITRO, AND EX VIVO CHARACTERIZATION - SOLIMAN, SARA M.; RASHWAN, KAREEM OMAR; TEAIMA, MAHMOUD; R. JASTI, BHASKARA; EL-NABARAWI, MOHAMED AHMED; ABDEL-HALEEM, KHALED M. (International Journal of Applied Pharmaceutics, 2022)
Objective: Transethosomes (TEs) have introduced an emerging avenue of interest in vesicular research for transdermal delivery of drugs and can be a proper delivery system for painkillers like NSAIDS. This study aimed to formulate and characterize the potential of TE to enhance the transdermal transport of Dexketoprofen trometamol (DKT) to achieve controlled pain management compared to DKT solution. Methods: Factorial design (23) was adopted to appraise the influence of independent variables, namely, Lipoid S100 and surfactant concentrations and surfactant type (X3) on the % solubilization efficiency (% SE), vesicle size (VS), and % release efficiency (% RE). Thin film hydration was the preferred approach for preparing TEs where vesicle size, zeta potential, polydispersity index, %SE and %RE were investigated. The optimized formula was nominated and subjected to several studies. For the permeation study, optimum TE was incorporated into carbapol gel base for comparison with DKT solution. Also, an accelerated stability study was assessed for optimized formula. Results: All the prepared DKT-loaded TEs revealed acceptable VS, PDI, and ZP. The highest %SE (86.08±1.05 %) and lowest %RE (44.62±1.36 %) were observed in case of F1. The optimized formula (F1) displayed VS of 133.2±1.62 nm, PDI of 0.342±0.03 and ZP of-21.6±2.45 mV. F1 revealed enhanced skin permeation of a 2.6-fold increase compared with DKT solution. Moreover, F1 was stable upon storage and a non-significant change (P>0.05) was observed. Conclusion: DKT was successfully incorporated into vesicle carrier and can signify an alternative option for providing this therapy, bypassing the poor bioavailability and considerable adverse consequences of using the oral route besides improved patient compliance.